2022
DOI: 10.1371/journal.pone.0265809
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative spontaneous self-talk and performance in gymnastics: The role of contextual, personal and situational factors

Abstract: The purpose of this study was to analyse whether contextual (perception of motivational climate and positive and negative spontaneous self-talk in sports), personal (positivity) and situational variables (positive and negative spontaneous self-talk employed in competition and precompetitive anxiety) predict performance in a competition of ensembles of rhythmic gymnastics. 258 female gymnasts between ages14 and 20 (M = 15.24, SD = 1.46) participated in the study, completing pre- and post-competition measures. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 59 publications
0
11
0
3
Order By: Relevance
“…This was a significant discovery because there was growing evidence linking harsh (or negative) self-talk to impulsive mood swings. Numerous writers, including Santos-Rosa et al [ 19 ], who discovered that performance was negatively impacted by negative self-talk, support these findings. They observed that positive self-talk was a predictor of positive performance.…”
Section: Discussionmentioning
confidence: 92%
“…This was a significant discovery because there was growing evidence linking harsh (or negative) self-talk to impulsive mood swings. Numerous writers, including Santos-Rosa et al [ 19 ], who discovered that performance was negatively impacted by negative self-talk, support these findings. They observed that positive self-talk was a predictor of positive performance.…”
Section: Discussionmentioning
confidence: 92%
“…The positive thinking activity will involve learning how to turn negative thoughts into positive ones. The practice will involve strengthening of positive self-talk to organize thoughts, assign positive meanings, and engage in silent or verbal self-dialog ( Santos-Rosa et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Penemuan ini menggariskan kesan berbeza daripada perbualan kendiri positif dan negatif terhadap kebimbangan dan prestasi dalam konteks eksperimen terkawal. Dapatan kajian ini hampir sama dengan hasil penyelidikan Santos-Rosa et al (2022) dan Lotfi et al (2016). Kedua-dua strategi perbualan kendiri negatif dan positif mempengaruhi tahap kebimbangan pra-pertandingan pemain badminton.…”
Section: Kesimpulanunclassified